The Effect of Kinesiotaping on Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis - Piri, Ebrahim; Jafarnezhadgero, AmirAli; Alihosseini, Saeid; Moradzade, Nastaran (International Journal of Sport Studies for Health, 2026)
Objective: Anterior cruciate ligament reconstruction (ACLR) is one of the most common orthopedic surgeries, and optimal functional recovery requires a precise and multifaceted rehabilitation program. Kinesio taping (KT) has emerged as a non-invasive adjunctive therapy for managing postoperative complications. This study aimed to systematically review and meta-analyze the effects of KT on balance, muscle strength, pain, and edema in patients following ACLR.Methods and Materials: A systematic search was conducted across six databases PubMed, Medline, Scopus, EMBASE, Google Scholar, and the Cochrane Central Register of Controlled Trials (CENTRAL) from 2014 until the final search date in February 2025. Eligible studies were randomized controlled trials (RCTs) evaluating the effects of KT in post-ACLR patients. Study quality was assessed using the Cochrane Risk of Bias tool (RoB 2). Data were pooled using a random-effects model, and the standardized mean difference (SMD) was calculated as the effect size.Findings: Thirteen studies with 631 participants were included in the final analysis. Meta-analysis revealed that KT was significantly associated with improved dynamic balance (SMD = 0.75, 95% CI: 0.33 to 1.17), increased quadriceps strength (SMD = 0.53, 95% CI: 0.19 to 0.87), reduced pain (SMD = 0.53, 95% CI: 0.22 to 0.85), and decreased edema (SMD = 1.01, 95% CI: 0.68 to 1.35). Heterogeneity across studies was low to moderate (I² = 45–68%).Conclusion: Current evidence supports KT as a safe and effective adjunctive intervention in ACLR rehabilitation, providing significant improvements in balance, muscle strength, pain, and swelling.